Enhancing Students’ Writing through Scaffolding and Writing Process Approach in Blended Learning - Anjarwati, Rosi; Sa'adah, Lailatus (Universitas Teuku Umar, 2024)
Writing English as a foreign language in academic setting requires students’ competence and creativity. Teacher or lecturer needs to apply an appropriate teaching method which can assist students to develop their potential writing skill. In addition, the development of technology enable teacher to conduct blended learning environment to facilitate students’ learning. This research aimed at investigating the effect of scaffolding and writing process in blended learning context. Quasi experimental research is utilized to know whether the combination of scaffolding and writing process give effect students’ writing achievement. Forty-nine students of English Department were involved as the participant of this study. Writing test in the form of pre-test and post-test were used to collect the data of students’ writing score. And then, the data was analyzed by using Analysis of Covariance (ANCOVA). The result indicates the significant effect of scaffolding and writing approach on students’ writing. The research’s finding may have implication for English teachers in writing courses as well as curriculum developer.